The Polymerization of MMA and ST to Prepare Material with Gradient Refractive Index in Electric Field - Yao Huang; Daming Wu; Dongyun Ren; Qingyun Meng; Xiaojun Di (Advances in Materials Science and Engineering)
Light scattering material with gradient refractive index was prepared under the electrical field by taking methyl methacrylate (MMA) monomer as the matrix with the addition of a little preheated styrene (ST) and peroxidation benzoin formyl (BPO). The material obtained under electrical field presented different transmittance and molecular weight at different parts of the cylindrical sample along the axis of the direction of electric field which led to the layering phenomenon and gradient refractive index. The disparity of molecular weight between different layers can be as much as 230 thousand. There were several peaks in the figure of GPC test of the sample under electric field. This proved that there were polymers with different molecular weights in the sample. Therefore, it can be concluded that electrical field has a significant effect on polymerization.